Neuropsychological Development of Cool and Hot Executive Functions Between 6 and 12 Years of Age: A Systematic Review - Fernández García, Laura; Merchán, Ana; Phillips-Silver, Jessica; Daza González, María Teresa (Frontiers in Psychology, 2021)
Previous studies on the development of executive functions (EFs) in middle childhood have traditionally focused on cognitive or “cool” EFs: mainly working memory, inhibitory control and cognitive flexibility. However, knowledge of the development of socio-emotional or “hot” EFs, such as delay of gratification, decision-making and theory of mind, is more limited. The main aims of this systematic review were to characterize the typical development of both the primary cool and hot EFs in middle childhood, and to identify the main tools for evaluating EFs as a whole. We conducted a systematic search on studies of cognitive and socio-emotional EFs published in the last 5 years in Pubmed, PsycInfo and WoS databases. Of 44 studies selected, we found a variety of tasks measuring cool EFs, while measures of hot EFs were limited. Nevertheless, the available data suggest that cool and hot components follow different developmental trajectories during middle childhood.